2018
DOI: 10.1136/bmjoq-2018-000483
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention to reduce treatment of asymptomatic bacteriuria in long-term care

Abstract: ObjectiveTo determine if an educational intervention can decrease the inappropriate antibiotic treatment of long-term care (LTC) residents with asymptomatic bacteriuria (ASB).DesignProspective chart audit between May and July 2017.SettingSeven LTC facilities in Regina, Saskatchewan, Canada.ParticipantsChart audits were performed on all LTC residents over 18 years of age with a positive urine culture. Educational sessions and tools were available to all clinical staff at participating LTC facilities.Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…One study evaluated the impact of an educational intervention to improve antibiotic use for UTIs in 10 Canadian LTCFs and reported a 26% decrease (adjusted incidence rate ratio=0.74, 95% CI: 0.47 to 0.74) in the overall number of antibiotic prescriptions per 1000 resident days 10. The second study, in seven Canadian LTCFs, reported a decrease in the use of antibiotics for asymptomatic bacteriuria from 90% pre-intervention to 62.9% post-intervention (p=0.003), following an educational intervention 73. The third study reported that the implementation of new guidelines and physician-pharmacy-nurse quality circles resulted in a 22% reduction in overall antibiotic use over a 6-year period 74.…”
Section: Discussionmentioning
confidence: 98%
“…One study evaluated the impact of an educational intervention to improve antibiotic use for UTIs in 10 Canadian LTCFs and reported a 26% decrease (adjusted incidence rate ratio=0.74, 95% CI: 0.47 to 0.74) in the overall number of antibiotic prescriptions per 1000 resident days 10. The second study, in seven Canadian LTCFs, reported a decrease in the use of antibiotics for asymptomatic bacteriuria from 90% pre-intervention to 62.9% post-intervention (p=0.003), following an educational intervention 73. The third study reported that the implementation of new guidelines and physician-pharmacy-nurse quality circles resulted in a 22% reduction in overall antibiotic use over a 6-year period 74.…”
Section: Discussionmentioning
confidence: 98%
“…Lee and colleagues undertook an evaluation of an educational intervention related to ASB in patients at 7 LTC facilities in Regina, Saskatchewan, Canada, with the primary outcome of percentage of residents who received inappropriate antibiotic treatment for ASB [23]. There was a pre-assessment period and a postassessment period of 5 weeks each, and the intervention took place during the 2 weeks in between.…”
Section: Resultsmentioning
confidence: 99%
“…Around the world, it has become evident that there is a need to strengthen medical education by avoiding the prescription of antimicrobials in cases that do not warrant it. In this study, we identified cases without indication for antimicrobial use, including asymptomatic bacteriuria (ASB) and colonization ( n = 17, 12.0%) [ 25 ]. Another issue to highlight is that no dosing adjustments were seen in eight hemodialyzed patients, bearing in mind that up to 50% of meropenem is removed during this process, and so a dose is required after each session [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%